Magnetic-field-driven topological phase transition in the holographic Weyl semimetal - Bruni, R. C.L.; Ferreira, Luiz F.; Rodrigues, Diego M. [UNESP] (American Physical Society (APS), 2023)
We study the magnetic field effects on the quantum critical point (QCP) in the holographic Weyl semimetal model. We show that it increases quadratically with the magnetic field for weak field and linearly with the magnetic field for strong field. Our findings are compatible with previous results in the literature from other approaches.